2020
DOI: 10.1097/01.aoa.0000652916.46974.79
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound Abnormalities in Late-Onset Severe Preeclampsia: Prevalence and Association With Serum Albumin and Brain Natriuretic Peptide

Abstract: (Anesth Analg. 2019;128(6):1208–1216) Care providers frequently use point-of-care ultrasound (POCUS) on pregnant women diagnosed with preeclampsia to prevent serious afflictions such as cerebral complications or cardiorespiratory failure. Present-day ultrasound research has found a number of indicators for pulmonary interstitial syndrome (PIS) and a higher optic nerve sheath diameter (ONSD), the latter of which could indicate elevated intracranial pressure. As of now, irregular laboratory markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 0 publications
1
39
1
Order By: Relevance
“…It is well known that PE patients have abnormally increased coagulation substances and clotting activity. 14,15 However, the study found that FIB in the PE group was increased and then decreased in the PE group; and was significantly higher in the middle pregnancy than in the early pregnancy, when compared with that in the normal twin pregnancy group. Although FIB was still higher in the late pregnancy than in the early pregnancy, but lower than in the middle pregnancy.…”
Section: Discussionmentioning
confidence: 84%
“…It is well known that PE patients have abnormally increased coagulation substances and clotting activity. 14,15 However, the study found that FIB in the PE group was increased and then decreased in the PE group; and was significantly higher in the middle pregnancy than in the early pregnancy, when compared with that in the normal twin pregnancy group. Although FIB was still higher in the late pregnancy than in the early pregnancy, but lower than in the middle pregnancy.…”
Section: Discussionmentioning
confidence: 84%
“…Studies on BNP in PE have mainly focused on its diagnosis or prediction of the disease and its relationship with the associated cardiovascular complications. In PE, the BNP levels reflect the severity of the PE (10)(11)(12)(13)(14), and elevated BNP levels are associated with ventricular systolic or diastolic dysfunction (24)(25)(26). Kumari et al (13) found that BNP levels in women with chronic hypertension and gestational hypertension who later superimposed or progressed to PE were significantly higher than those who did not develop PE, and the ROC curve analysis showed that BNP had a good value in predicting the development of PE in the study population (AUC =0.7406, 95% CI: 0.6543-0.827, P<0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac dysfunction plays an important role in the occurrence of PIS, and the BNP level has good specificity in predicting cardiac dysfunction. Therefore, the BNP level can indirectly reflect the occurrence of PIS (24). The study by Yu et al (31) used velocity vector imaging combined with BNP levels to study the ventricular functions of fetuses in women with PE, showed that the fetuses of mothers with PE had biventricular diastolic and systolic dysfunction, and the increase of fetal umbilical vein BNP levels were significantly correlated with the dysfunction (Spearman coefficient was 0.615-0.703).…”
Section: Discussionmentioning
confidence: 99%
“…The POCUS helped narrow the differential rapidly and facilitate immediate treatment. There has been support for POCUS examination of the lungs, heart, and optic nerve sheath diameter to help detect the presence of pulmonary interstitial edema, cerebral edema, and/or cardiac dysfunction while managing patients with pre-eclampsia and eclampsia [ 13 ]. Some managing critically ill pregnant women suggest opportunities for further use of multiorgan POCUS including transcranial Doppler and transcranial color-coded duplex sonography which are not traditionally done in the ED setting [ 14 ].…”
Section: Discussionmentioning
confidence: 99%